Estratégias de alavancagem do poder de voto e o valor das empresas brasileiras de capital aberto - Lelis Pedro de Andrade (2017)
Since the early 2000s, the Brazilian legal and institutional environment faced some changes, especially regarding the grant of the voting right for all shares. However, while the dual class shares issuance has been decreasing since these institutional changes, we still know little on the reasons why the controlling shareholders would accept to give up some of their voting power. Furthermore, we argue that the previous literature has not tested in the Brazilian market the possibility of the controlling shareholder decide accept a possible pressure for adopting practices of corporate governance deemed better according with the market, but, at the same time, include the possibility to him find substitutes or indirect mechanisms to leverage the voting power, which would enable he implement some different and effective anti-takeover strategies. Thus, this thesis aims to verify what are the sources that leverage the voting power which enable the controlling shareholder to adopt the entrenchment practice, rather than alignment practice in the Brazilian stock market. So, we take into account different possible mechanisms, such as the dual class shares issuance, the indirect ownership structure, the shareholders' agreement (SA), the possible undue obedience from the directors to the Chief Executive Officer (CEO) and/or the controlling shareholder, and the presence of institutional investors, which are the possible direct and indirect sources to leverage the voting power by the controlling shareholder, and potentially adopt the possible preference to consuming private benefits of control rather than maximize the firm value in the Brazilian stock market. To this end, we take into account a panel data with 462 firms that provided 3057 observations collected during the period 2000 and 2012, and we employed different techniques to analyze the data, such as univariate statistics, regressions using OLS, panel data models, logit and probit models, and the two-step model of Heckman that aims to mitigate the possible self-selection bias of the sample. We divided the results into four main conclusions. The first is related to the context of the Brazilian stock market, which favors the emergence of pyramidal or indirect structures, which provide costs and benefits at the firm level. The second refers to the identification of a possible new agency cost associated with the excess of alignment between the outside directors and the firm's controlling shareholder, even if the controlling shareholder choose adopt the entrenchment practices. The third conclusion is regarding to the fact that the shareholders' agreement tends to be an alternative mechanism to leverage the voting power of the largest shareholder, which is consistent with the argument that the divergence, rather than the convergence of interests, is a relevant point that the possible corporate governance reform should take into account by practitioners and academics in the Brazilian stock market. The fourth is related to the identification of another indirect source to leverage the voting power of the largest shareholder, which is the participation of institutional investors, such as banks and/or pension funds, once the evidence show that such investors surprisingly are able to reduce the agency conflict between shareholders and creditors, however, it occurs possibly at the expense of minority shareholders. We interpreted that these findings have important theoretical implications in future studies on corporate governance, once they indicate that the recommendations of best corporate governance practices that overlook the assumptions of the agency theory, especially when applying it in the Brazilian market, can exert unforeseen effects on the development of corporate governance and, hence, on the firm's value in the Brazilians stock market.